Volatility Correlation Dynamics Between the US and Asia-Pasific. Empirical Evidence - Zhou, Huimin (2016)
With the globalization and liberalization of international trade and finance, the interaction between international financial markets has increased markedly. Thus, this paper examines the nature of linkage among equity market returns and their volatility, with a particular focus on the global financial crises in 2008 for Australia, Hong Kong, Japan, Korea and the US. This paper applies EGARCH model and VAR model with 5 min-average stock indices data spanning from 04 April 2000 to 31 September 2014. Based on the result from EGARCH model, it can be found that the US stock market has significant influence on returns of another four stock markets throughout pre-, during-, post- the 2008 global economic slump. It implies that volatility spillover effects from all five stock markets have bidirectional relationships from the conditional variance. For the result from VAR techniques, compared with Asia-Pasific stock markets, the US market is the one that is less influenced by another 4 shocks. Meanwhile, the US innovation has relative high impact on Australia and Hong Kong while has less impact on Korea as well as Japan. Both the EGARCH and VAR models show that the US stock market is the most influential market towards volatilities of smaller economies. However, it is obvious that after that crush, the US equity market has slightly fewer reaction on other markets compared with the result in pre-financial crisis.